Biological analysis of flexor tendon repair-failure stump tissue: A potential recycling of tissue for tendon regeneration - Lu, C-C. (Bone Joint Res, 2019)
OBJECTIVES: Re-rupture is common after primary flexor tendon repair. Characterization of the biological changes in the ruptured tendon stumps would be helpful, not only to understand the biological responses to the failed tendon repair, but also to investigate if the tendon stumps could be used as a recycling biomaterial for tendon regeneration in the secondary grafting surgery. METHODS: A canine flexor tendon repair and failure model was used. Following six weeks of repair failure, the tendon stumps were analyzed and characterized as isolated tendon-derived stem cells (TDSCs). RESULTS: Failed-repair stump tissue showed cellular accumulation of crumpled and disoriented collagen fibres. Compared with normal tendon, stump tissue had significantly higher gene expression of collagens I and III, matrix metalloproteinases (MMPs), vascular endothelial growth factor (VEGF), platelet-derived growth factor (PDGF), and insulin-like growth factor (IGF). The stump TDSCs presented both mesenchymal stem and haematopoietic cell markers with significantly increased expression of CD34, CD44, and CD90 markers. Stump TDSCs exhibited similar migration but a lower proliferation rate, as well as similar osteogenic differentiation but a lower chondrogenic/adipogenic differentiation capability, compared with normal TDSCs. Stump TDSCs also showed increasing levels of SRY-box 2 (Sox2), octamer-binding transcription factor 4 (Oct4), tenomodulin (TNMD), and scleraxis (Scx) protein and gene expression. CONCLUSION: We found that a failed repair stump had increased cellularity that preserved both mesenchymal and haematopoietic stem cell characteristics, with higher collagen synthesis, MMP, and growth factor gene expression. This study provides evidence that tendon stump tissue has regenerative potential. Cite this article: C-C. Lu, T. Zhang, R. L. Reisdorf, P. C. Amadio, K-N. An, S. L. Moran, A. Gingery, C. Zhao. Biological analysis of flexor tendon repair-failure stump tissue: A potential recycling of tissue for tendon regeneration. Bone Joint Res 2019;8:232–245. DOI: 10.1302/2046-3758.86.BJR-2018-0239.R1.